A proposed instrument for assessing organizational citizenship behavior in BFSI companies in India - Shaad Habeeb (Cogent Business & Management, 2019)
Though Organizational Citizenship Behavior is unenforceable by the organization, it promotes the effective functioning of the organization through a discretionary individual behavior of employees. In this regard, Organizational Citizenship Behavior contributes to the organization in many ways. However, due to cultural differences, dimensions of Organizational Citizenship Behavior may differ from country to country. In line with that, this paper explores the creation of an instrument for assessing Organizational Citizenship Behavior based on a study done in a Hindi-English environment involving public and private companies in the banking, finance, and insurance industry in India. Taking into account the high turbulence and considerable staff attrition in the banking, finance, and insurance sector that additionally increases pressure on employees to be effective performers within a stressful environment, this study intended to examine dimensions of Organizational Citizenship Behavior in this industry in New Delhi and the National Capital Territory of India. The study has used a descriptive research design and the quantitative approach. Specific items for the Organizational Citizenship Behavior assessment were selected for their reliability and quality using exploratory factor analysis and confirmatory factor analysis. The specific steps involved in these processes and resulting item inclusion are discussed in detail.
Keywords: L2; M0; M1; Y1; 650; extra role behavior; Hindi-English environment; OCB dimensions; rating scale; banking & insurance sector